PROSES PERALIHAN TANAH YANG DIKUASAI NEGARA UNTUK DIJADIKAN HAK GUNA BANGUNAN DI KANTOR ATR/BPN KOTA DENPASAR - Kusuma Wardhani, Sang Ayu Made Ary; Sulistyawati, Ni Putu Yunika; Riswama, I Dewa Gede Putra (Kerta Dyatmika, 2024)
Individual rights over land encompass various forms, including land rights, land waqf, ownership rights, security rights (hak tanggungan), and strata title rights (ownership of apartment units). In legal terms, the transfer of land rights may occur through specific juridical acts. This study aims to examine the process of transferring state-controlled land into Building Use Rights (Hak Guna Bangunan/HGB) at the Office of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) of Denpasar City. The research adopts an empirical juridical method, combining secondary data in the form of legal materials with primary data obtained through field research. The findings reveal that the transfer process is initiated through the applicant’s request for the issuance of a deed of Building Use Rights by the Land Deed Official (Pejabat Pembuat Akta Tanah/PPAT), in accordance with Article 24 paragraph (4) of Government Regulation No. 40 of 1996 concerning Building Use Rights. Upon completion of the deed, the Denpasar City Land Office issues a Building Use Rights Certificate based on the Decree of Granting HGB. However, several obstacles are encountered in the process, including issues related to registration, the limited duration of Building Use Rights, procedural difficulties in the renewal process, and the influence of spatial planning (master plan). In conclusion, while the normative procedures are well-established, the practical implementation remains constrained by technical and administrative challenges, necessitating comprehensive and coordinated solutions.